The action model of the Social Innovation : Observatory of the Social Innovation Science Park - Rocha Jiménez, Daniel; Rueda Lizarazo, Hortencia; Chaparro Guevara, Rosa Alexandra (Cooperativismo & Desarrollo, 2016)
Purpose: This article aims to explain the actions of the Social Innovation Observatory (ois by its Spanish initials) that are aligned with the strategic focus of the Social Innovation Science Park (pcis), which are related to transforming communities and tracking the management of knowledge and ois processes, methods, and tools. Topics: The pcis has a particular model of management, complex for its combination of the obscure term “science park” that is derived, on the one hand, from the market economy and, on the other, the polyvalent and polysemic concept of social innovation that is still under construction and is associated with the problems and challenges of society. Development: In this context we find the ois, a management unit of the pcis that is dedicated to monitoring the environment in search of opportunities and challenges in communities. It also searches for means to address these challenges such as knowledge and technologies. Its operations have closely adhered to the model shown here since 2013. Conclusions:The ois fulfills an important role in the observation of the processes of community transformation, both outcomes and impacts, as well as those processes related to environmental monitoring. It additionally observes traditional knowledge, opportunities, challenges, and technologies.
Keywords: knowledge management; social innovation; social innovation observatory; community transformation